Bone morphogenetic proteins in tumour associated angiogenesis and implication in cancer therapies. Issue 2 (1st October 2016) - Ye, Lin; Jiang, Wen G.
Highlights: BMPs play a critical role in embryonic and postnatal development, and also in maintaining homeostasis in different organs and tissues. They play important roles in the development and progression of certain malignancies. BMPs are also involved in tumour associated angiogenesis. BMP can regulate the functions of vascular endothelial cells directly, or indirectly by regulating angiogenic factors expression. Abstract: Bone morphogenetic protein (BMP) belongs to transforming growth factor-β superfamily. To date, more than 20 BMPs have been identified in humans. BMPs play a critical role in embryonic and postnatal development, and also in maintaining homeostasis in different organs and tissues by regulating cell differentiation, proliferation, survival and motility. They play important roles in the development and progression of certain malignancies, including prostate cancer, breast cancer, lung cancer, etc. Recently, more evidence shows that BMPs are also involved in tumour associated angiogenesis. For example BMP can either directly regulate the functions of vascular endothelial cells or indirectly influence the angiogenesis via regulation of angiogenic factors, such as vascular endothelial growth factor (VEGF). Such crosstalk can also be reflected in the interaction with other angiogenic factors, like hepatocyte growth factor (HGF) and basic fibroblast growth factor (bFGF). All these factors are involved in the orchestration of the angiogenic process during tumour development and progression. Review of the relevant studies will provide a comprehensive prospective on current understanding and shed light on the corresponding therapeutic opportunity.